2017
DOI: 10.1002/cbic.201600561
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Activity‐Based Probe to Monitor Family GH59 Galactosylceramidase, the Enzyme Deficient in Krabbe Disease

Abstract: Galactosylceramidase (GALC) is the lysosomal β-galactosidase responsible for the hydrolysis of galactosylceramide. Inherited deficiency in GALC causes Krabbe disease, a devastating neurological disorder characterized by accumulation of galactosylceramide and its deacylated counterpart, the toxic sphingoid base galactosylsphingosine (psychosine). We report the design and application of a fluorescently tagged activity-based probe (ABP) for the sensitive and specific labeling of active GALC molecules from various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…ABPP using cyclophellitol-derived probes allows for rapid evaluation GBA activity in patient tissues, and can identify GBA G samples with sensitivity comparable to immunoblotting (a considerably more laborious technique) [10]. Use of suitably configured ABPs has also demonstrated that lysosomal -glucosidase, lysosomal -galactocerebrosidase, and lysosomal -galactosidase are all amenable to ABPP profiling, opening up avenues for the rapid diagnosis of Pompe [34], Krabbe [50] and Fabry [32] diseases respectively. Interestingly, the irreversible inhibitory nature of many ABPs can also be used to in vivo.…”
Section: Recent Developments In the Glycosidase Abp Field 41 Glycosmentioning
confidence: 99%
“…ABPP using cyclophellitol-derived probes allows for rapid evaluation GBA activity in patient tissues, and can identify GBA G samples with sensitivity comparable to immunoblotting (a considerably more laborious technique) [10]. Use of suitably configured ABPs has also demonstrated that lysosomal -glucosidase, lysosomal -galactocerebrosidase, and lysosomal -galactosidase are all amenable to ABPP profiling, opening up avenues for the rapid diagnosis of Pompe [34], Krabbe [50] and Fabry [32] diseases respectively. Interestingly, the irreversible inhibitory nature of many ABPs can also be used to in vivo.…”
Section: Recent Developments In the Glycosidase Abp Field 41 Glycosmentioning
confidence: 99%
“…Subsequently, cyclophellitol aziridine ABPs with attached reporter groups via alkyl or acyl linkers were designed reacting with multiple retaining glycosidases in the same class [55,59]. Cyclophellitol aziridine ABPs labeling α-galactosidases, α-glucosidases, α-fucosidase, α-iduronidase, β-galactosidases, and β-glucuronidase, as well as cyclophellitol ABPs labelling galactocerebrosidase, were designed [60][61][62][63][64][65]. Applications of ABPs are the quantitative detection and localization of glycosidases in cells and tissues, as well as identification and characterization of glycosidase inhibitors by competitive ABP profiling [66,67].…”
Section: Gcase Protein and Life Cyclementioning
confidence: 99%
“…A variety of ABPs have been described for different enzyme classes (Table 1) 8,9 . An ABP can be specific for one enzyme (tailored probe) 10 or can target a group of enzymes sharing recognition or reactivity (broad-spectrum probe) 11 . Broad-spectrum probes can be used for competitive ABPP (Fig.…”
Section: Abppmentioning
confidence: 99%